Extracellular Vesicles Generated by Gram-Positive Bacteria Protect Human Tissues Ex Vivo From HIV-1 Infection - Costantini, Paolo E.; Vanpouille, Christophe; Firrincieli, Andrea; Cappelletti, Martina; Margolis, Leonid; Ñahui Palomino, Rogers A. (Frontiers in Cellular and Infection Microbiology, 2022)
Vaginal microbiota dominated by lactobacilli protects women from sexually transmitted infection, in particular HIV-1. This protection is, in part, mediated by Lactobacillus-released extracellular vesicles (EVs). Here, we investigated whether EVs derived from other Gram-positive bacteria also present in healthy vaginas, in particular Staphylococcus aureus, Gardnerella vaginalis, Enterococcus faecium, and Enterococcus faecalis, can affect vaginal HIV-1 infection. We found that EVs released by these bacteria protect human cervico-vaginal tissues ex vivo and isolated cells from HIV-1 infection by inhibiting HIV-1-cell receptor interactions. This inhibition was associated with a diminished exposure of viral Env by steric hindrance of gp120 or gp120 modification evidenced by the failure of EV-treated virions to bind to nanoparticle-coupled anti-Env antibodies. Furthermore, we found that protein components associated with EV’s outer surface are critical for EV-mediated protection from HIV-1 infection since treatment of bacteria-released EVs with proteinase K abolished their anti-HIV-1 effect. We identified numerous EV-associated proteins that may be involved in this protection. The identification of EVs with specific proteins that suppress HIV-1 may lead to the development of novel strategies for the prevention of HIV-1 transmission.